Comprehension of prosody in Huntington's disease. - Speedie, L J (1990)
Patients with Huntington's Disease (HD) who were without dementia were compared to unilateral stroke patients and controls as previously reported in 1983, to discover if they had a prosodic defect. Subjects were presented tape-recorded speech filtered sentences and asked to indicate the tone of voice as happy, sad or angry (affective prosody), or as a question, command or statement (propositional prosody). HD patients were impaired in comprehension of both types of prosody compared to controls but were not different from stroke patients. A second study compared early HD patients with at-risk siblings and spouse controls on comprehension of affective and propositional prosody, discrimination of both types of prosody, rhythm discrimination and tonal memory (Seashore tests). HD patients were impaired in both comprehension and discrimination of all types of prosody. HD patients were less accurate than at-risk patients on the tonal memory task but not on the rhythm discrimination task. These findings suggest compromise in ability to understand the more subtle prosodic aspects of communication which may contribute to social impairment of HD patients very early in the course of the disease.